1979
DOI: 10.1017/s0031182000053762
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and killing ofTrypanosoma dionisiiby human neutrophils, eosinophils and monocytes

Abstract: SUMMARYThe cell-mediated resistance of human leucocytes toTrypanosoma dionisii, a bat parasite related toT. cruzi, was investigated. Human peripheral blood neutrophils and monocytes were cytotoxic toT. dionisiias assessed by electron microscopy and by induction of99mTc release from trypanosomes pre-labelled with [99mTc]pertechnetate. The enhancement of cytotoxicity by specific antiserum varied considerably from one individual to another. Neither blood lymphocytes nor blood eosinophils induced99mTc release from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 19 publications
0
10
0
3
Order By: Relevance
“…Cline et al (1968) later showed in vitro phagocytosis of Gram-positive Staphylococcus aureus and Gram-negative Escherichia Coli bacteria, and living and dead Candida albicans , by human eosinophils purified from patients with eosinophilia. Eosinophils have also been shown to phagocytose and destroy parasites such as T. dionisii , but only in the presence of antiserum (Thorne et al 1979). Eosinophilic phagocytosis is accompanied by degranulation and involves lysosomal enzymes, similarly to neutrophils.…”
Section: Innate Immune Functions Of Eosinophilsmentioning
confidence: 99%
“…Cline et al (1968) later showed in vitro phagocytosis of Gram-positive Staphylococcus aureus and Gram-negative Escherichia Coli bacteria, and living and dead Candida albicans , by human eosinophils purified from patients with eosinophilia. Eosinophils have also been shown to phagocytose and destroy parasites such as T. dionisii , but only in the presence of antiserum (Thorne et al 1979). Eosinophilic phagocytosis is accompanied by degranulation and involves lysosomal enzymes, similarly to neutrophils.…”
Section: Innate Immune Functions Of Eosinophilsmentioning
confidence: 99%
“…Eosinophils may play an important role in the defense of the organism against certain parasites such as Schistosoma (Mahmoud et al 1975;Butterworth et al 1979), Trichinella (Grove et al 1977;Smithers et al 1977) and Trypanosoma (Sanderson and Jennifer 1978 ;Sanderson and De Souza 1979;Thorne et al 1979). In the case of large parasites the eosinophils attach and discharge the content of their specific granules on the surface of opsonized parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody facilitates phagocytosis of T cruzi 142,451 and T dionisii [43], and may be important in extracellular killing of T cruzi by PMN [46,47]. MPO inhibitors (azide, cyanide, diethyldithiocarbamate) abolished the toxicity of PMN to L donovani [48] and T dionisii [30,44], supporting a role for MPO in mediating cidal activity. Electron microscopy demonstrated the release of granule material into the phagosome following ingestion of T cruzi trypomastigotes by rat neutrophils and eosinophils 1421.…”
Section: Toxicity Of Oxygen-dependent Mlcroblcldal Systems Against Prmentioning
confidence: 99%
“…Neutrophils, in which MPO comprises up to 5 % of the dry weight of the cell, effectively ingest and kill T gondii [41], L donovani promastigotes [34] and amastigotes [32], T cruzi trypomastigotes [42], and T dionisii epimastigotes and trypomastigotes [43,44]. Antibody facilitates phagocytosis of T cruzi 142,451 and T dionisii [43], and may be important in extracellular killing of T cruzi by PMN [46,47]. MPO inhibitors (azide, cyanide, diethyldithiocarbamate) abolished the toxicity of PMN to L donovani [48] and T dionisii [30,44], supporting a role for MPO in mediating cidal activity.…”
Section: Toxicity Of Oxygen-dependent Mlcroblcldal Systems Against Prmentioning
confidence: 99%